2017
DOI: 10.1159/000478659
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adenosinergic Modulation on Cytokine Levels in a Pentylenetetrazole-Induced Generalized Tonic-Clonic Seizure Model

Abstract: Objective: It has been suggested that the adenosinergic system and cytokines play a role in the pathogenesis of epilepsy. Although the role of the adenosinergic system in the modulation of seizure activity is well known, the mechanism of this modulation needs to be described in detail. We performed this study to determine the contribution of the proinflammatory cytokines to the generalized seizure activity during adenosine and caffeine treatment. Methods: We induced generalized tonic-clonic seizures with the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
3
1
0
Order By: Relevance
“…Numerous in ammatory mediators, including soluble polypeptides known as cytokines, play a crucial role in both the activation of innate immunity and the transition to adaptive immunity. Ils and TNFs are two of these molecules (40).Through previous studies, it was concluded that PTZ increased the level of in ammatory cytokines such as TNF-α and IL-1β in the brain via activation of microglia and astrocytes (39) (41). Our ndings were consistent with previous research.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous in ammatory mediators, including soluble polypeptides known as cytokines, play a crucial role in both the activation of innate immunity and the transition to adaptive immunity. Ils and TNFs are two of these molecules (40).Through previous studies, it was concluded that PTZ increased the level of in ammatory cytokines such as TNF-α and IL-1β in the brain via activation of microglia and astrocytes (39) (41). Our ndings were consistent with previous research.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we show that there is increase in IL-1β levels chronic PTZ models in the cortex (Figure 2 Show that IL-1β may be associated with the both epileptic seizure and epileptogenesis. Our findings of IL-1β levels in acute and chronic PTZ models is consistent one of the previous studies which are carried out in rat and mice brain [15,20,23]. According to our findings, it may be suggested that TNF-α is assotiated with epileptogenesis, while IL-1β is related to both acute seizure and epileprogenesis.…”
Section: Proinflammatory Cytokines In Acute and Chronic Ptz Modelssupporting
confidence: 92%
“…These findings show that TNF-α raises after epileptogenesis and is not related to acute epileptic seizures. Our findings of TNF-α levels in acute PTZ model is coherent one of the previous study [15]. On the other hand, some studies have shown the increase in TNF-α levels after a single PTZ induced seizures dose in total brain and serum in contrast to our study [16,17].…”
Section: Proinflammatory Cytokines In Acute and Chronic Ptz Modelssupporting
confidence: 91%
“…Elevated levels of proinflammatory cytokines have been identified in the CSF of patients with refractory SE (Wang & Chen, 2018). Generalized seizure pathogenesis has also been associated with cytokines -TNF-a, IL-1B and IL-6 (Dede et al, 2017). The increased cytokine levels suggested in COVID-19 may explain the high incidence of status epilepticus and generalized seizures in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%